Digitalizing Culture in Education: A Local Wisdom-Based E-Book on Balinese Songs for Fourth Graders - Kristina, Ni Kadek Sindy Dwi; Sujana, I Wayan; Suniasih, Ni Wayan (Universitas Pendidikan Ganesha, 2024)
This study was motivated by the inability of educators or teachers to provide engaging and innovative learning media. This issue significantly impacts students' learning outcomes, which remain low or below the Minimum Competency Criteria (KKM). Therefore, it is essential to develop a learning medium that addresses students' learning challenges. The aim of this research is to develop a local wisdom-based electronic book (E-Book) focusing on Balinese songs with the theme